Biochar for sustainable applications: Advances in characterization, activation, and life cycle assessment - Himanshu; Deepanshu Awasthi; Prathvi Raj Chauhan; Deepti; Rakesh Godara; Kunwar Pal; Vandit Vijay (Biomass and Bioenergy, 2026)

Prediction of crack initiation and crack damage thresholds of disparate rocks using machine learning models - Abhinesh Kourav; Deepanshu Shirole; Sankhaneel Sinha (Arabian Journal of Geosciences, 2026)

Impact of Thermal Damage on the Full-Field Deformational Behavior of Agaria Marble Under Uniaxial Loading - Girish Chand; Deepanshu Shirole; Mohammadreza Aghajanzadeh; Hossein Masoumi (Rock Mechanics and Rock Engineering, 2026)

Examining the Changes in Precipitation Patterns Across the Western Himalayan Region During the Winter Season - Deepanshu Tiwari; Sushant Das; Pyarimohan Maharana; P. R. Tiwari (International Journal of Climatology, 2026)
The Himalayas are associated with ever‐challenging topography and changing dynamic climatic conditions. The climatological winter precipitation was studied over the Western Himalayan region (WHR) during two time periods spanning 30 years each (1961–1990 and 1993–2022) using ERA5 reanalysis. Analysis illustrates that the decline of the large‐scale precipitation is much more prominent than convective precipitation over the WHR. Although large‐scale precipitation decreases, a greater fraction of it falls as rain rather than snow, partially offsetting the reduction in snowfall. The study reveals that the atmospheric dynamics favours the influx of moisture into the study domain; however, the combination of the rising temperatures, which increase the water‐holding capacity of the atmosphere, and the decreasing strength of vertical winds reduces the updraft, resulting in a greater decline in precipitation in recent times. Further, the decreased transport of moisture into the upper troposphere leads to a decline in the cloud micro‐physical parameters that support large‐scale precipitation. The study also revealed that, although the number of western disturbances (WDs) and WD days are on the rise, their track density passing through the WHR has declined due to a northward shift, resulting in a decrease in the large‐scale precipitation. These findings indicate potential shifts in precipitation types and patterns, which could have significant climatic implications for the regional hydrological cycle.

Vegetation loss and climate-driven fragmentation in the Himalayan alpine ecosystem: an AI/ML-based LULC and carbon stock analysis - Akash Kashyap; Vijendra Kumar Pandey; Dipankar Bera; Deepanshu Parashar; Ashwani Kumar; Arvind Pandey; Sajid Ullah; Wafa Saleh Alkhuraiji; Mohamed Zhran (Theoretical and Applied Climatology, 2026)

Identification and Characterization of NAC Transcription Factor-Based Simple Sequence Repeat Markers and Genome-Wide Association Studies for Seed Longevity in Alliums - Deepanshu Jayaswal; Deepesh Kumar; Nandita Banerjee; Ankit Badesra; Himanshu Sharma; Garima Yadav; Sanjay Kumar; Rajiv Baliram Kale; Kuldip Jayaswall (Plant Molecular Biology Reporter, 2026)

Design of Bifunctional Luliconazole–Metronidazole Co-Crystals for Antifungal and Antibacterial Therapy in Atopic Dermatitis - C. Nithya Shanthi; Ram Prasad; Deepanshu Rana; Riya Mahar; Arun Mahato (Journal of Pharmaceutical Innovation, 2026)

Assessment of thermal damage in intact rocks via linear and diffused ultrasonics coupled with full-field strains analyses - Anita Verma; Deepanshu Shirole (International Journal of Rock Mechanics and Mining Sciences, 2026)

Evaluation of broad-spectrum antimicrobial efficacy of biogenic NiO/CuO nanocomposite: In vitro, in silico, and molecular docking approach - Shalu Yadav; Ankit Singh; Deepanshu Rana; Abhay Kumar Choubey; Praveen Kumar Srivastava (Biomass and Bioenergy, 2026)

Network pharmacology, molecular docking, and In Vitro evaluation of morin against gastric cancer - Nilesh Naskar; Sunil Kumar; Deepanshu Mamgai; Harish Chandra Vishwakarma; Santosh Kumar Guru; Bijo Mathew; Naseer Maliyakkal; Uday R. Kumar; Shweta Shrivastava; Manish Kumar Jeengar (Molecular Diversity, 2026)

Genome-Wide Association and Transcriptome Analysis Unraveling Putative Genes Responsible for High TSS of Allium cepa - Deepanshu Jayaswal; Deepesh Kumar; Vijay Mahajan; Nandita Banerjee; Sonia Sood; Isha Sharma; Sanjay Kumar; Kuldip Jayaswall (Journal of Plant Growth Regulation, 2026)

Improvement and strengthening of silica sand with electric fields: an electrodeposition approach - Vandana Brar; Deepanshu Shirole; Sovik Das (Bulletin of Engineering Geology and the Environment, 2026)

Ayurveda and endophytes for sustainable agriculture: bridging traditional knowledge with modern nanotechnology - Nikhil Kumar; Ramesh Chandra Dubey; Surbhi Pradhan; Deepanshu Rana; Vipin Nautiyal; Prashant Katiyar (Nanotechnology for Environmental Engineering, 2026)

Whole Genome Sequencing and Subtractive Genomics of Lipaphis erysimi: A Vital Pest of Brassica juncea - Deepanshu Jayaswal; Ratna Prabha; Kuldeep Kumar; Deepesh Kumar; Kuldip Jayaswall; Archana Anokhe; Arvind Nath Singh; Sanjay Kumar; Rekha Kansal (Journal of Plant Growth Regulation, 2026)

Extracellular Protein Quality Control in Tau Pathology - Prasun Kumar Bhunia; Deepanshu Verma; Priyanka Vimal; Prasad Kasturi (Molecular Neurobiology, 2026)

Extraction of bioactive compounds from marine brown seaweed - Deepanshu Bhatt; Himanshu Tomar; Rajveer Singh; Shivani Chandel (Regional Studies in Marine Science, 2025)

An Amalgamation of Dynamic DNA and Two Novel Chaotic Maps for Satellite Image Encryption - Mohit Dua; Suraj Singh Jadon; Anant Raghuvanshi; Deepanshu Vishwakarma; Shelza Dua; Deepti Dhingra (Journal of the Indian Society of Remote Sensing, 2025)

Immunomodulator and marker-assisted identification of Allium genotypes containing immunological memory against anthracnose - Kuldip Jayaswall; Deepesh Kumar; Deepanshu Jayaswal; R. Sagar; Sanjay Kumar; Ram Kumar Sharma; Kiran Bhagat; Vijay Mahajan; Himanshu Sharma; Surendra Pratap Singh; Isha sharma (Physiological and Molecular Plant Pathology, 2025)

Effect of Primary Air on Performance of a Natural Draft Dual-Purpose Gasifier Stove: An Experimental Study - Himanshu; Deepanshu Awasthi; Kunwar Pal (BioEnergy Research, 2025)

Proteolytic efficiency and degradation of gliadin and toxic immunopeptide in laboratory media by indigenous potential probiotic Bacillus strains - Anjali Jaglan; Gunjan Sadera; Deepanshu; Gunjan Goel (Food and Humanity, 2025)

Heterogeneous interface mismatch-manipulated ruthenium-immobilized binary metal phosphide-layered 2D V2CTx for high-efficiency water electrolysis - Deepanshu Malhotra; Duy Thanh Tran; Sampath Prabhakaran; Do Hwan Kim; Nam Hoon Kim; Joong Hee Lee (Chemical Engineering Journal, 2025)

Handling objective preference and variable uncertainty in evolutionary multi-objective optimization - Deepanshu Yadav; Palaniappan Ramu; Kalyanmoy Deb (Swarm and Evolutionary Computation, 2025)

Conformational Transitions in EGFR Protein Tyrosine Kinase Domain and Their Modulation by Mutants - Eshrat Shaikh; Varun Talati; Deepanshu Garg; Ashay Baruah; Priyanka Joshi; Virupaksha Bastikar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Deciphering genetic diversity and population structure of onion (Allium cepa L.) using agro-morphological and molecular markers - Shorya Kapoor; Sonia Sood; Kuldip Jayaswall; Vinod Kumar Sood; Nimit Kumar; Tamanna Sood; Deepanshu Jayaswal; Vakul Sood (Horticulture, Environment, and Biotechnology, 2025)

Allium sativum and Allium cepa offer excellent potential for introgression and production of allicin and high total soluble solids into closely related wild Alliums - Kuldip Jayaswall; Deepesh Kumar; Deepanshu Jayaswal; Himanshu Sharma; Sanjay Kumar; Chibuikem Unamba (South African Journal of Botany, 2025)

Investigating bi-decadal precipitation changes over the Northwest Himalayas during the pre-monsoon: role of Pacific decadal oscillations - Deepanshu Aggarwal; Rohit Chakraborty; Raju Attada (Climate Dynamics, 2024)

Development of Allium cepa potential intron polymorphism markers for molecular breeding of Alliums - Kuldip Jayaswall; R. Sagar; Deepanshu Jayaswal; Akash Kumar; Surendra Pratap Singh; Romit Seth; Himanshu Sharma; Deepesh Kumar; Vijay Mahajan; Sanjay Kumar; Major Singh (South African Journal of Botany, 2024)

Use of machine learning-based classification algorithms in the monitoring of Land Use and Land Cover practices in a hilly terrain - Deepanshu Parashar; Ashwani Kumar; Sarita Palni; Arvind Pandey; Anjaney Singh; Ajit Pratap Singh (Environmental Monitoring and Assessment, 2024)

Development of chloroplast derived SSR markers for genus Allium and their characterization in the allies for genetic improvement of Alliums - Kuldip Jayaswall; Himanshu Sharma; Deepanshu Jayaswal; R. Sagar; Abhishek Bhandawat; Akash Kumar; Isha Sharma; Pratibha Chaturvedi; Dalasanuru Chandregowda Manjunathagowda; Deepesh Kumar; Vijay Mahajan; Sanjay Kumar; et al. (South African Journal of Botany, 2023)

Retraction Note to: Ocimum basilicum attenuates ethidium bromide-induced cognitive deficits and pre-frontal cortical neuroinflammation, astrogliosis and mitochondrial dysfunction in rats - Debapriya Garabadu; Deepanshu Singh (Metabolic Brain Disease, 2023)

Impact of climate on vegetation in Pindari watershed of Western Himalayas, Kumaun, India, using spatiotemporal analysis: 1972–2018 - Arvind Pandey; Deepanshu Parashar; Naveen Chandra Bhatt; Sarita Palni; Charu Pundir; Arvind Singh Yadav; Ajit Pratap Singh; Pankaj Kumar Bhatt (Environmental Science and Pollution Research, 2022)

Identification and characterization of chickpea genotypes for early flowering and higher seed germination through molecular markers - Garima Yadav; Deepanshu Jayaswal; Kuldip Jayaswall; Abhishek Bhandawat; ArvindNath Singh; Jyotsana Tilgam; Abhishek Kumar Rai; Rachna Chaturvedi; Ashutosh Kumar; Sanjay Kumar; S. P. Jeevan Kumar (Molecular Biology Reports, 2022)

Assessment of snout analysis of Himalayan glaciers: impact studies on Pindari, Kafni, Sundardhunga, and Baljuri base camp glaciers - Arvind Pandey; Deepanshu Parashar; Bidyutjyoti Baruah; Sarita Palni; Arvind Singh Yadav; Ajit Pratap Singh; Pankaj Kumar Bhatt; Charu Pundir (Environmental Monitoring and Assessment, 2022)

Chloroplast derived SSRs reveals genetic relationships in domesticated alliums and wild relatives - Kuldip Jayaswall; Himanshu Sharma; Abhishek Bhandawat; R. Sagar; Deepanshu Jayaswal; Akash Kumar; Pratibha Chaturvedi; Vijay Mahajan; Sanjay Kumar; Major Singh (Genetic Resources and Crop Evolution, 2022)

Success of microbial genes based transgenic crops: Bt and beyond Bt - Jyotsana Tilgam; Kuldeep Kumar; Deepanshu Jayaswal; Sharani Choudhury; Adarsh Kumar; Kuldip Jayaswall; Anil Kumar Saxena (Molecular Biology Reports, 2021)

COVID-19 and Gut Microbiota: A Potential Connection - Swati Rajput; Deepanshu Paliwal; Manisha Naithani; Aashish Kothari; Kiran Meena; Satyavati Rana (Indian Journal of Clinical Biochemistry, 2021)

Evaluation of an Ultrasonic Method for Damage Characterization of Brittle Rocks - Deepanshu Shirole; Ahmadreza Hedayat; Ehsan Ghazanfari; Gabriel Walton (Rock Mechanics and Rock Engineering, 2020)

RETRACTED ARTICLE:Ocimum basilicum attenuates ethidium bromide-induced cognitive deficits and pre-frontal cortical neuroinflammation, astrogliosis and mitochondrial dysfunction in rats - Debapriya Garabadu; Deepanshu Singh (Metabolic Brain Disease, 2020)

Super refractory status epilepticus in a patient with insulinoma - Surjya P. Choudhury; Deepanshu Dubey; Jayantee Kalita; Usha K. Misra (Acta Neurologica Belgica, 2019)

Influence of Gassing Agent and Density on Detonation Velocity of Bulk Emulsion Explosives - Arvind Kumar Mishra; Manamohan Rout; Deepanshu Ranjan Singh; Sakti Pada Jana (Geotechnical and Geological Engineering, 2018)

Improved Stability and Enhanced Oral Bioavailability of Atorvastatin Loaded Stearic Acid Modified Gelatin Nanoparticles - Deepanshu Shilpi; Varun Kushwah; Ashish Kumar Agrawal; Sanyog Jain (Pharmaceutical Research, 2017)